2021
DOI: 10.3390/jcm10215009
|View full text |Cite
|
Sign up to set email alerts
|

Macular Structure–Function Relationships of All Retinal Layers in Primary Open-Angle Glaucoma Assessed by Microperimetry and 8 × 8 Posterior Pole Analysis of OCT

Abstract: Purpose: The aim of this study is too correlate the sensitivity and thickness values of intraretinal layers at macula in healthy eyes and primary open-angle glaucoma (POAG) eyes. Methods: The thickness of different intraretinal segmentations was estimated by means of optical coherence tomography (OCT) Spectralis (Heidelberg, Engineering, Inc., Heidelberg, Germany) with the posterior pole analysis program 8 × 8 in 91 eyes from 91 patients (60 with glaucoma and 31 healthy patients). Macular sensitivity was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Furthermore, in primary open‐angle glaucoma, negative correlations were found between retinal sensitivity, as assessed by microperimetry, and the thicknesses of the macular ORLs, but positive correlations were also found for the IRL. These structure–function relationships showed different behaviour depending on the retinal layer considered in agreement with our finding in the older age group (Garcia‐Medina et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, in primary open‐angle glaucoma, negative correlations were found between retinal sensitivity, as assessed by microperimetry, and the thicknesses of the macular ORLs, but positive correlations were also found for the IRL. These structure–function relationships showed different behaviour depending on the retinal layer considered in agreement with our finding in the older age group (Garcia‐Medina et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…In glaucoma, RGC axons in the inferior hemisphere have been found to be most susceptible to glaucomatous damage (Na et al, 2011; Nakatani et al, 2011), and the inferior outer sector in the macular area was shown to have the greater diagnostic capacity (Na et al, 2011), and inferior inner macular volume to correlate most with visual field mean deviation (Nakatani et al, 2011). Furthermore, in a study in persons with primary open‐angle glaucoma, correlations detected between retinal sensitivity measured by microperimetry and macular GC layer thickness were stronger in the inferior hemisphere (Garcia‐Medina et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thickness value of the other segmentations was also obtained by summing up the thicknesses of the automatically obtained segmentations as follows: ganglion cell complex (RNFL + GCL + IPL), middle retina (INL + OPL + ONL), IPL + INL and OPL + ONL ( Figure 1 a). The thicknesses of OPL and ONL were not considered individually and were summed up, as was performed in previous works regarding autism [ 15 ] and glaucoma [ 16 , 17 , 18 ], because these two layers are hard to be conveniently separated in OCT images due to their similar reflectivity. A three-dimensional video ( Video S1 ) has been made in order to better understand the integration of cross-sectional ( Figure 1 a) and en face OCT images ( Figure 1 b,c).…”
Section: Methodsmentioning
confidence: 99%
“…Garcia-Medina et al [ 28 ] carried out the work “Macular structure-function relationships of all retinal layers in primary open-angle glaucoma assessed by microperimetry and 8 × 8 posterior pole analysis of OCT”. The authors fully demonstrated that glaucoma eyes displayed more structure–function relationships than healthy eyes.…”
mentioning
confidence: 99%